Analisis Postur Kerja Operator Pemanen Kelapa Sawit dengan Metode Quick Exposure Check (QEC) - Faradila Ananda Yul (Jurnal Surya Teknika, 2021)
Sandria Sukses Bersama is a company engaged in oil palm plantations. Oil palm harvesting activities are carried out using egrek tools. The activity is carried out on hilly land which is quite steep with the age of 16 years old oil palm trees with tree heights reaching 10-15 meters. This condition causes operators to tend to tilt their heads up when doing work so operators often complain of feeling pain in their necks and legs. This study was conducted with the aim of analyzing the work posture of oil palm harvesting operators in carrying out their work. The results of this study indicate that the operator's exposure score with an average of 88.97%. This value is at exposure level 4 which is 71-100% which indicates that the working posture of oil palm harvesting at PT. Sandria Sukses Bersama needs to take action now because it is very risky for work-related injuries if it is carried out continuously.